Activity‐Based Probes for 15‐Lipoxygenase‐1. (9th September 2016) - Eleftheriadis, Nikolaos; Thee, Stephanie A.; Zwinderman, Martijn R. H.; Leus, Niek G. J.; Dekker, Frank J.
Abstract: Human 15‐lipoxygenase‐1 (15‐LOX‐1) plays an important role in several inflammatory lung diseases, such as asthma, COPD, and chronic bronchitis, as well as various CNS diseases, such as Alzheimer's disease, Parkinson's disease, and stroke. Activity‐based probes of 15‐LOX‐1 are required to explore the role of this enzyme further and to enable drug discovery. In this study, we developed a 15‐LOX‐1 activity‐based probe for the efficient activity‐based labeling of recombinant 15‐LOX‐1. 15‐LOX‐1‐dependent labeling in cell lysates and tissue samples was also possible. To mimic the natural substrate of the enzyme, we designed activity‐based probes that covalently bind to the active enzyme and include a terminal alkene as a chemical reporter for the bioorthogonal linkage of a detectable functionality through an oxidative Heck reaction. The activity‐based labeling of 15‐LOX‐1 should enable the investigation and identification of this enzyme in complex biological samples, thus opening up completely new opportunities for drug discovery.